Analisis Pertumbuhan dan Upaya Optimasi Penerimaan Pajak Hotel di Kota Tangerang Selatan - Ariangga, Damal; Utaminingtyas, Tri Hesti; Perdana, Petrolis Nusa (LPPM Universitas Negeri Jakarta, 2024)
This research aims to exploring the growth rate of hotel tax revenues which in South Tangerang City in 2018-2022 and also the optimization efforts carried out by the Bapenda in increasing hotel tax revenues. This research use qualitative approach with descriptive method. This research consist of three informants with purposive sampling technique was used. The results of this research show that the growth rate of hotel tax revenues in South Tangerang City in the 2018-2022 period experienced fluctuating growth with a growth value of 9.67% in 2019 into unsuccessful criteria, -35.83% in 2020 into unsuccessful criteria, 17.84% in 2021 into unsuccessful criteria, and 31.11% in 2022 into has not been successful criteria. Meanwhile, the optimization efforts carried out by the Bapenda to increase hotel tax revenues through regional tax optimization strategy indicators have not been fully implemented well. Bapenda has only implemented two strategies out of five optimization strategies.